Correlation of MRI lesions with visual psychophysical deficit in secondary progressive multiple sclerosis - Caruana, P A; Davies, M B; Weatherby, S J; Williams, R; Haq, N; Foster, D H; Hawkins, C P (Brain (London, England : 1878), 2000)
The aim of this work was, first, to clarify the nature of the relationship between the sensory deficit in the demyelinated visual pathway and morphological changes revealed by MRI and, secondly, to test whether there was a preferential effect of demyelination for either the magnocellular or parvocellular pathway in established multiple sclerosis. Twenty-four patients with secondary progressive multiple sclerosis were studied psychophysically and by MRI of the optic nerve and brain. MRI was performed with a Phillips (0.5T) scanner. Visual pathway MRI lesion load was evaluated independently using the total optic nerve lesion length and lesion area seen on STIR (short inversion time inversion recovery) images of the optic nerve and the total post-chiasmal lesion area on T(1)-, T(2)- and proton-density-weighted images of the brain. Psychophysical tests determined 75%-seeing thresholds for horizontal gratings consisting of isoluminant red and green sinusoids of the same spatial frequency combined out-of-phase for preferential stimulation of the parvocellular system and in-phase for preferential stimulation of the magnocellular system. It was found that, in this group of patients, visual psychophysical loss was significantly correlated with lesion area seen on proton density MRI sequences of the post-chiasmal visual pathway, and that the parvocellular pathway was more affected than the magnocellular pathway, especially at lower spatial frequencies.